Extended nitric oxide analysis in patients with chronic rhinosinusitis with nasal polyps, with or without associated asthma. (4th November 2020) - Paoletti, Giovanni; Melone, Giulio; Guida, Giuseppe; Pirola, Francesca; Malvezzi, Luca; Pelaia, Corrado; Mariani, Alessia; Racca, Francesca; Malipiero, Giacomo; Ferri, Sebastian; Puggioni, Francesca; Spriano, Giuseppe; et al.
Abstract: Chronic rhinosinusitis with nasal polyps (CRSwNP) is a complex inflammatory disease highly impacting patient's quality of life, and associated with lower airway inflammation often evolving into asthma. Exhaled nitric oxide (FENO ) is a non-invasive tool to assess Type 2 airway inflammation and its extended analysis allows to differentiate between alveolar concentration (CalvNO) and bronchial output (JawNO). It is also possible to assess the sino-nasal production of nitric oxide (nNO). We studied extended nitric oxide production in patients with CRSwNP with or without associated asthma. Consecutive adult patients with CRSwNP, with or without asthma, and 15 healthy controls were enrolled. Exclusion criteria were: smoking, uncontrolled asthma, recent upper or lower airway infections and oral corticosteroid therapy in the 4 weeks preceding clinical evaluation. Patients' demographic and clinical data were collected; patients underwent pulmonary function tests and extended nitric oxide analysis including nasal nNO assessment. A total of 125 subjects were enrolled (15 healthy controls; 69 with CRSwNP and asthma, and 41 with CRSwNP only). FENO, JawNO and CalvNO values were higher, while nNO was lower, in all patients with CRSwNP compared to healthy controls; no difference was found in CalvNO between patients with concomitant asthma and non-asthmatic subjects; in asthmatic patients, FENO and JawNO were significantly higher, while nNO values was lower, compared to patients with CRSwNP only. These results suggest that CRSwNP could be the first manifestation of a more complex systemic inflammatory pathology driven by Type 2 inflammation. An 'inflammatory gradient' hypothesis could describe a pattern of inflammation in CRSwNP patients that starts distally in the alveoli. Finally, our study indirectly reinforces the concept that novel biological drugs could become valid therapeutic options for nasal polyposis.